Die skoolorde van Genève 1559: ’n Basis vir ’n gereformeerde skoolorde - Meijer, Gerard J. (Koers, 2014)
The school order of Genève 1559: A basis for a reformed school order. Calvin and education are synonymous. Apart from his written legacy, which speaks of his intense love for education, he endeavoured to put schools in place where young people could be educated in the ways of the Lord. This was not only in the curriculum, but also in the way it was presented and the teachers who presented those lessons received special attention from Calvin. The light of God’s Word is shed over everything. This article shows how, given his own historical background and the tools available to him, he tried to develop a school system in the city of Geneva where children could be educated in accordance with the promise of their parents at their baptism. The school order of Geneva (1559) in conjunction with the Genevan Church order (1561) gives us insight in the doings and thoughts of Calvin on education. I hope to indicate some lines that could be of use in the present dialogue on educational matters. Sadly, the way Calvin set up a system for education is no longer evident in schools. Isn’t there an urgent need for a well-defined and fundamental school order amongst all the school policies and rules? This question will receive attention in the article.